Impact of Doom Scrolling on Mental Well-being among Media Students in Karachi - Usman, Sobia; Huma, Tazeen; Akbar, Muhmmad Rashid (Annals of Human and Social Sciences, 2025)
This study assess the psychological effects of doom scrolling on the mental health of media students in Karachi. Doom scrolling the habitual consumption of negative news on social media has been linked to growing mental health issues, particularly among youth. This mixed-method study targeted undergraduate and postgraduate media students in Karachi. The population included students from seven universities: Iqra University (all campuses), University of Karachi, SZABIST, Bahria University, IOBM, Ilma University, and Indus University. A sample of 1000 students was selected via stratified random sampling for surveys, and 15 students exhibiting high doom scrolling behavior were chosen through purposive sampling for interviews. Tools included a structured questionnaire and a semi-structured interview guide. SPSS and thematic coding were used for analysis. A strong positive correlation (r = 0.672, p < 0.05) was found between doom scrolling and symptoms like anxiety, emotional exhaustion, and poor sleep. Interview responses validated these findings. Implement media literacy programs, provide mental health support, and promote healthy digital habits across university campuses.